The Effectiveness of Infographics to Enhance Students' Vocabulary Mastery at Eighth Grade Students of SMPN 1 Kota Tangerang Selatan - Zukhruf, She Darin; Juniardi, Yudi; Miranty, Delsa (Globish: An English-Indonesian Journal for English, Education, and Culture, 2024)
This research aimed to determine if using infographics in the eighth grade at SMPN 1 Kota Tangerang Selatan had a significant effect on students' vocabulary mastery. This study employed a quantitative approach and a quasi-experimental design. A total of 78 students participated in the study; 39 from each of the two classes (the experimental and control) were included in the sample. Each class took a pre-and post-test during the first and last meetings. Independent sample t-tests were run in SPSS version 22 to evaluate the hypothesis. The results showed that using infographics enhanced the vocabulary mastery of eighth-graders at SMPN 1 Kota Tangerang Selatan. The effect size was 0.80, with a significance level of 0.001 for the two-tailed Independent T-test (0.001 < 0.05). That supports the moderate size effect and indicates the acceptance of the alternative hypothesis. Thus, using an infographic as a teaching tool provides a significant effect on students' vocabulary mastery.